2018
DOI: 10.1007/s00384-018-3055-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute uncomplicated diverticulitis without antibiotics: risk factors for treatment failure

Abstract: PurposeConservative treatment strategy without antibiotics in patients with uncomplicated diverticulitis (UD) has proven to be safe. The aim of the current study is to assess the clinical course of UD patients who were initially treated without antibiotics and to identify risk factors for treatment failure.MethodsA retrospective cohort study was performed including all patients with a CT-proven episode of UD (defined as modified Hinchey 1A). Only non-immunocompromised patients who presented without signs of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
0
26
0
3
Order By: Relevance
“…These statements focused their attention on three topics under active debate. The first statement claims about the safety of ambulatory treatment of uncomplicated AD, which is safe and effective [73][74][75][76][77][78][79]. Moreover, this approach has also a significant impact on cost-saving [79].…”
Section: Commentsmentioning
confidence: 99%
“…These statements focused their attention on three topics under active debate. The first statement claims about the safety of ambulatory treatment of uncomplicated AD, which is safe and effective [73][74][75][76][77][78][79]. Moreover, this approach has also a significant impact on cost-saving [79].…”
Section: Commentsmentioning
confidence: 99%
“…In order to evaluate risk factors in those patients who experienced non‐antibiotic treatment failure, a retrospective cohort study of 565 patients with CT‐proven AUD who were initially treated with antibiotics was carried out (30‐day follow up) 29 . In a multivariable analysis of the study, patients with AUD and a CRP level >170 mg/L were found to be at higher risk for non‐antibiotic treatment failure 29 . Despite such studies to identify risk factors that may help clinical decision making, the impact of acute episodes of diverticulitis on patients’ quality of life renders observational, non‐interventional treatment decisions difficult for both patients and physicians.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that high C-reactive protein (CRP) level (>170 mg/ml) [12] or initial computer tomography (CT) findings of fluid collection and longer inflamed colon [13] could be useful factors in selecting patients who could benefit from antibiotic treatment, but these preliminary data need to be confirmed by further studies.…”
Section: Evidence Promentioning
confidence: 99%